Hepatitis C Virus Core Protein Transforms Murine Fibroblasts by Promoting Genomic Instability - Irina S. Smirnova; Nikolai D. Aksenov; Elena V. Kashuba; Pawan Payakurel; Vadim V. Grabovetsky; Alexei D. Zaberezhny; Maxim S. Vonsky; Lubov Buchinska; Peter Biberfeld; Jorma Hinkula; Maria G. Isaguliants (Cellular Oncology)
The oncogenic potential of hepatitis C virus (HCV) core protein has been demonstrated, but the precise mechanism of cell transformation triggered by HCV core is still unclear. This study shows that constitutive expression of HCV core protein (core) in NIH 3T3 murine fibroblasts triggers malignant transformation. At the preneoplastic stage, clones that expressed HCV core constitutively demonstrated genomic instability seen as disruption of the mitotic spindle cell checkpoint leading to increased ploidy. Transformation was completed by the loss of DNA and resistance to apoptosis induced by serum starvation. Simultaneously, cells acquired a capacity for anchorage independent growth and absence of contact inhibition. Inoculation of these transformed cells into severe combined immune deficiency (SCID) mice led to formation of solid core-expressing tumors. Transformation and tumorigenicity of core-expressing cell lines coincided with a 5- to 10-fold repression of endogenous p53 transactivation. Thus, long-term HCV core expression alone is sufficient for complete transformation of immortal fibroblasts that can then induce tumors in a susceptible host. This data suggests that malignant transformation by HCV core may occur through primary stress, induction of genomic instability, and further HCV core-induced rescue of surviving mutated cells.